The impact of breastfeeding during the third stage of labor on postpartum haemorrhage according to Higham Chart among women Attending Maternity Teaching Hospital in Sulaimani City - Saeed, Mahabat Hassan; Mohammed, Atiya K. (Sulaimani Journal for Pure and Applied Sciences, 2021)
One of the most important factor influencing the maternal health is postpartum haemorrhage. Immediate breastfeeding after birth is beneficial for releasing natural oxytocin that led to contracting uterus and reducing hemorrhage. To identify the impacts of breastfeeding on postpartum haemorrhage based on Higham chart. The design, a quasi-experimental study, post-test, only control was applied. Non- probability purposive was as sampling technique. Data collection was continued from 26th of February 2020 to 30th of July 2020. Three hundred women were selected from labor word, in the labor ward; these parturient women were equally divided into experimental group, applying early initiation of breastfeeding and control group, following the routine hospital care. In addition to a questionnaire, Pictorial Blood Assessment Cart (PBAC) was used to investigate the postpartum bleeding pattern of women in the labor's third stage. The chart of pictorial blood assessment is according to the presence of clots and the visual appearance of stained pads. According to Higham chart, in the experimental group, within 300 mothers 130 (86.7%) had a mild postpartum haemorrhage, 18 (12.0%) had a moderate postpartum haemorrhage and only 2 (1.3%) had severe postpartum haemorrhage; where in the control group, 32.7% and 30.7% of the women developed severe and moderate postpartum hemorrhage respectively. It is revealed that the extent of postpartum hemorrhage of the experimental group was greatly lower than the control group. Breastfeeding immediately after the birth is effective for decreasing the postpartum hemorrhage.
Keywords: Breastfeeding; Higham Chart; Postpartum haemorrhage; Third stage of labor